2003
DOI: 10.1097/00000542-200301000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic–Pharmacodynamic Modeling of Rocuronium in Case of a Decreased Number of Acetylcholine Receptors

Abstract: Both the Sheiner model and the unbound receptor model may be used to fit plasma concentration-effect data of rocuronium in pigs. The unbound receptor concentration model, however, can explain the observed differences in the time course of effect, based on receptor concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, it has been suggested that myotonic discharges may substitute for normal background nerve activity and thus suppress the expression of nicotinic acetylcholine receptors [5, 6]. A smaller number of nicotinic acetylcholine receptors can enhance susceptibility to non‐depolarising agents [16], which can explain the prolonged recovery following a given dose of drug that we have found in patient 4 suffering from severe MD1. On purely theoretical grounds it can be speculated that, in addition to changes at the neuromuscular junctions, alterations to the pharmacokinetics of neuromuscular blocking drugs could also be a potential cause for an exaggerated response to rocuronium.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, it has been suggested that myotonic discharges may substitute for normal background nerve activity and thus suppress the expression of nicotinic acetylcholine receptors [5, 6]. A smaller number of nicotinic acetylcholine receptors can enhance susceptibility to non‐depolarising agents [16], which can explain the prolonged recovery following a given dose of drug that we have found in patient 4 suffering from severe MD1. On purely theoretical grounds it can be speculated that, in addition to changes at the neuromuscular junctions, alterations to the pharmacokinetics of neuromuscular blocking drugs could also be a potential cause for an exaggerated response to rocuronium.…”
Section: Discussionmentioning
confidence: 79%
“…Both normal responses [8–11] and increased sensitivity and prolonged recovery have been reported [9, 11–15]. Structural changes at the neuromuscular junctions and decreased numbers of nicotinic acetylcholine receptors at postsynaptic membranes [5, 6] can explain these exaggerated responses to non‐depolarising agents [16]. Because of this unpredictability, neuromuscular block should be carefully monitored.…”
mentioning
confidence: 99%
“…This technique was applied also for PK-PD analysis, using the sequential PK-PD method and nonparametric PK method [9][10][11]. A method for simultaneous PK-PD analysis with an ITSB technique has not yet been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported pharmacodynamic models3, 4, 19 do not consider the interaction between acetylcholine (ACh) and the postsynaptic receptors at the motor endplates and are thus unsuitable for simulations of twitch strength in these two conditions. In this study, we have amplified our previously published model of neuromuscular transmission 13.…”
mentioning
confidence: 99%